Efisiensi Penyisihan Parameter COD, BOD5, dan NH3-N pada Pengolahan Air Limbah Kawasan Industri Menggunakan Moving Bed Biofilm Reactor (MBBR) - Putri, Irviani Syaiful; Alfiah, Taty (Environmental Engineering Journal ITATS, 2025)
This research is conducted on a laboratory scale. The wastewater used in this study is raw wastewater collected from the wastewater treatment plant (WWTP) of an industrial area. The wastewater was taken from the equalization tank unit, while the microbial inoculum was taken from the clarifier unit. The MBBR reactor was built from PVC pipe with a volume of 10 L, filled with 20% Kaldnes K1 media and 80% wastewater based on reactor volume. The MBBR effluent was measured for pH, BOD5, COD, and NH₃-N over eleven days. The research results show that the industrial area wastewater at NIP exceeded the quality standards for COD, BOD₅, NH₃-N, and NO₃-N parameters. Wastewater treatment using MBBR technology with Kaldnes K1 media achieved removal efficiencies of 71.8%, 83.5%, and 69.6% for BOD5, COD, and NH₃-N, respectively. The MBBR biological treatment reduced BOD5, COD, and NH₃-N values from 160.6 mg/L, 379.1 mg/L, and 26 mg/L to 42.5 mg/L, 62.4 mg/L, and 7.9 mg/L, respectively. The MBBR effluent from industrial area wastewater treatment has met the applicable quality standards. MBBR technology is a promising wastewater treatment method suitable for various types of wastewater.